Balai Rehabilitasi Anak Trauma di Tabanan - Wulandari, Ni Made Eny; Dwijendra, Ngakan Ketut Acwin; Kastawan, I Wayan (Jurnal Arsitektur Universitas Udayana, 2022)
The lack of a more specific child care center has an impact on increasing the number of cases related to children experiencing mental disorders due to traum. The prevalence rate of cases of children experiencing trauma due to victims of bullying, natural disasters, and families who are not as prosperous, especially in Bali, has increased every year, the highest number of cases is in Buleleng Regency. From these problems, this article will discuss the application of the zoning concept on the site for the design of a trauma child rehabilitation center located in Baturiti Village, Tabanan Regency which is the chosen alternatif as a place that meets the requirements to design a Trauma Child Rehabilitation Center. The approach method used is to take aspects of traditional Balinese architectural values, one of which is the concept of sanga mandala. The function of the building and the characteristics of the site are taken into consideration for the application of the building zoning concept to be applied. The zoning concept is determined by taking the values ??from the sanga mandala conception which  can produce a transitional space suitable for the design of this  rehabilitation center .